Fibroblast Activation Protein‐α Responsive Peptide Assembling Prodrug Nanoparticles for Remodeling the Immunosuppressive Microenvironment and Boosting Cancer Immunotherapy. Issue 9 (16th December 2021) - Sun, Mengqi; Yao, Shaobo; Fan, Linyang; Fang, Zhiguo; Miao, Weibing; Hu, Zhiyuan; Wang, Zihua
Abstract: Checkpoint blockade immunotherapy has broad application prospects in the clinical treatment of malignant tumors. However, the low response rate of the checkpoint blockade is due to low tumor immunogenicity and immunosuppression within the tumor microenvironment. Herein, the authors design an amphiphilic bifunctional PD‐1/PD‐L1 peptide antagonist PCP, and co‐deliver doxorubicin (DOX) and R848 through co‐assembly of a multi‐agent prodrug (PCP@R848/DOX), which can be specifically cleaved by fibroblast activation protein‐α (FAP‐α) in the tumor stroma. Upon reaching the tumor tissue, the PCP@R848/DOX prodrug nanostructure is disassembled by FAP‐α. The localized release of DOX and R848 triggers immunogenic cell death (ICD) and reprograms tumor‐associated macrophages (TAMs) to elicit antitumor immunity. Furthermore, sustained release of PD‐1 or PD‐L1 peptide antagonists mediates the PD‐L1 pathway blockade for further propagated activation of cytotoxic T lymphocytes. Notably, a tumor microenvironment activatable prodrug nanoparticle is presented for triple‐modality cancer therapy that functions by simultaneously activating ICD and altering the phenotype of TAMs when combined with PD‐1 blockade therapy, which efficiently elicits a strong systemic antitumor immune response. This strategy may emerge as a new paradigm in the treatment of cancer by combination immunotherapy. Abstract : This study develops an amphiphilic bifunctional PD‐1/PD‐L1 peptide antagonist PCP, and through codelivery of doxorubicin (DOX) and R848, triggers immunogenic cell death and reprograms tumor‐associated macrophages to elicit antitumor immunity. The combination R848, DOX, and immune checkpoint blockade molecules (PD‐L1/PD‐1 peptide antagonist) can cooperatively modulate the immunosuppressive tumor microenvironment for improved cancer immunotherapy.